Collaborative Governance: Membangun Solusi Bersama Dalam Penanggulangan Stunting - Herni, Herni; Tahir, Nurbiah; Arfah, Sitti Rahmawati (Kolaborasi : Jurnal Administrasi Publik, 2024)
Stunting is a condition of body failure in children due to chronic malnutrition, so children become too short for their age. The purpose of this study was to analyse Stunting Prevention in Barugae Village, Duampanua District, Pinrang Regency using the Collaborative Governance Model. This research uses qualitative research methods. The data collection techniques used were observation, interviews and documentation. The results of this study indicate that collaboration is quite effective by looking at initial conditions, institutional design regarding basic rules in stunting prevention, leadership and Collaborative processes in implementing stunting prevention programmes. However, there are several obstacles in the collaboration to overcome stunting in Barugae Village, namely the lack of awareness among mothers of toddlers about child nutrition. Then, there is a lack of awareness of mothers to bring their children to the Posyandu, as well as people who are entitled to WC but do not have land.